An experimental nonlinear low dynamic stiffness device for shock isolation. (7th July 2015) - Francisco Ledezma-Ramirez, Diego; Ferguson, Neil S.; Brennan, Michael J.; Tang, Bin
Abstract: The problem of shock generated vibration is very common in practice and difficult to isolate due to the high levels of excitation involved and its transient nature. If not properly isolated it could lead to large transmitted forces and displacements. Typically, classical shock isolation relies on the use of passive stiffness elements to absorb energy by deformation and some damping mechanism to dissipate residual vibration. The approach of using nonlinear stiffness elements is explored in this paper, focusing in providing an isolation system with low dynamic stiffness. The possibilities of using such a configuration for a shock mount are studied experimentally following previous theoretical models. The model studied considers electromagnets and permanent magnets in order to obtain nonlinear stiffness forces using different voltage configurations. It is found that the stiffness nonlinearities could be advantageous in improving shock isolation in terms of absolute displacement and acceleration response when compared with linear elastic elements. Abstract : Highlights: The fundamentals of shock isolation and nonlinear low dynamic stiffness are briefly reviewed. An experimental model is presented based on previous theoretical assumptions. The properties of the model are presented experimentally. i.e. natural frequency, dynamic stiffness, equivalent damping. Shock response is evaluated experimentally by applying pulses of different duration and amplitude. It is concluded that low dynamic stiffness is beneficial for improving shock isolation in terms of acceleration, but not for relative displacement.